Characterisation of PTCD1 and CRYAB variants in rare and mitochondrial disease pathogenesis using gene editing - Mantegna, Jessica Lee (Curtin University, 2024)
Mitochondrial diseases are highly complex, debilitating conditions impacting 1 in every 6,000 to 8,000 live births. Investigation of patient variants by generating cellular models is vital to a timely and accurate diagnosis. This thesis demonstrates the first instance of combining prime editing systems with engineered pegRNAs into one plasmid for delivery into mammalian cells, identified the first disease-causing variant in PTCD1, and characterised three variants in CRYAB to investigate contribution to mitochondrial disease and dysfunction.